The work relative value estimation assessment in China: an empirical research for common surgical procedures - Hao, Jin; Yao, Han; Kong, Ling; Liu, Yuanli (Frontiers in Public Health, 2024)
Objectives China's National Health Service Items Standard (NHSIS) establishes a relative value system and plays an important role in pricing. However, there are few empirical evaluations of the objectivity of the NHSIS-estimated relative value. Methods This paper presents a comparison between physician work relative value units (wRVUs) estimates for 70 common surgical procedures from NHSIS and those from the U.S. Medicare Physician Fee Schedule (MPFS). We defined the ratio of the wRVUs for sample procedures to the benchmark procedure (inguinal hernia repair) as a standardized relative value unit (SRVU), which was used to standardize the data for both schedules. We examined the variances in the ranking and quantification of SRVUs across specialties and procedures, as well as how SRVUs impact procedure reimbursement prices between the two schedules. Results There was no systematic difference between MHSIS-estimated SRVUs and MPFS-estimated, but the dispersion of MPFS-estimated SRVU was greater than that of MHSIS-estimated, and the discrepancies increased with surgical risk and technical complexity. The discrepancies of SRVUs were significant in cardiothoracic procedures. Additionally, whether SRVUs were based on MPFS or MHSIS, there was a positive association between them and payment prices. However, in terms of the impact of SRVUs on payment pricing, the NHSIS system was lower than the MPFS system. Conclusions China has made incremental progress in estimating the relative value of healthcare services, but there are shortcomings in valuation methods and their impact on pricing. The modular assessment method should be considered as a component to optimize reform.